5. Meeting of the Technical Advisory Committee of Plant Protection Directors Santo Domingo (Rep. Dominicana) 8-14 Nov 1987. - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
124 páginas